1980
DOI: 10.1002/tera.1420210202
|View full text |Cite
|
Sign up to set email alerts
|

A study of spontaneoulsy aborted twins

Abstract: Fifty-three pairs of twins were obtained during examination of 1,939 spontaneously aborted complete embryos and fetuses. Therefore, the rate of twinning in pregnancies which spontaneously aborted was about 1 in 35. The spontaneous twin abortions consisted of 25 sets of twin embryos, 26 sets of twin fetuses, and two sets in which one was an embryo and one was a fetus. It was possible to determine the zygosity in 37 pairs. The ratio of monozygotic to dizygotic was 17.5:1. About 88% of the twin embryos and 21% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 2 publications
1
21
1
1
Order By: Relevance
“…Based on the fetopathological studies of all twin fetuses in his practice, Livingston and Poland [20] reported some kind of malformation in 21%, which is slightly higher than the figures for twin and triple miscarriages in our sample at 14 and 16%, respectively. According to the results by Arteaga et al [1] , in the case of multiple pregnancies the incidence of congenital malformation was around 25-30% higher than in singleton pregnancies.…”
Section: Discussioncontrasting
confidence: 38%
“…Based on the fetopathological studies of all twin fetuses in his practice, Livingston and Poland [20] reported some kind of malformation in 21%, which is slightly higher than the figures for twin and triple miscarriages in our sample at 14 and 16%, respectively. According to the results by Arteaga et al [1] , in the case of multiple pregnancies the incidence of congenital malformation was around 25-30% higher than in singleton pregnancies.…”
Section: Discussioncontrasting
confidence: 38%
“…The following mechanisms are implicated as possible causes of this anomaly: (1) early amnion rupture before obliteration of the extraembryonic coelom [3]; (2) abnormal splitting of the embryo at 4 gestational weeks [3]; (3) disturbance of the blood flow due to vascular rupture, as described in cocaine users [4][5][6] and (4) a special situation in monozygotic twins [7][8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have studied the frequency of twinning among spontaneously aborted gestational material; their results range from 0.3% to 20% [3,12,23]. One recent study found 53 twin pairs among 1,939 spontaneous abortions, for a frequency of 2.7% [23].…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found 53 twin pairs among 1,939 spontaneous abortions, for a frequency of 2.7% [23].…”
Section: Introductionmentioning
confidence: 99%